Pelatihan Pembelajaran Konsep dan Operasi Hitung Bilangan Cacah Menggunakan Block Dienes - Maniboey, Lidwina Cornelia; Sukmawati, Sukmawati (Universitas Cenderawasih, 2023)
Students need an understanding of the concept of place value to learn arithmetic operations on two-digit, three-digit, four-digit numbers, and so on. If students do not have an understanding of the concept of place value, students will have difficulty learning arithmetic operations that require the concept of place value. If students do not experience learning the formation of the concept of place value, namely the formation of the concept of tens of ten units, the concept of hundreds of tens of tens, the relationship between the concepts of units, tens and hundreds can become disconnected, so students cannot see a relationship between the three concepts and cannot use the relationship between these concepts to solve the arithmetic operations problem. Therefore training is needed in preparing and using media about place value. The purpose of implementing this PKM activity is to train teachers to be able to prepare and use Block Dienes media for the formation of concepts and operations for calculating place value, by implementing Bruner's learning theory in carrying out learning activities about place value. The method for implementing PKM activities is carried out in three stages, including preparation, implementation and evaluation. After attending the training the participants are able to understand the use of the dienes block in determining place value.